Possible Features of Learning Management System to Improve Writing Skill - Yunika Triana; Dewi Zulaiha (Presscience, 2022)
In this modern era, many models are offered in teaching English. Apart from a variety of strategies, there are also many media platforms that offer new ways of teaching. LMS base teaching that offers different media and ways of teaching. In this study, researchers describe an online learning concept by increasing the variety of activity models to improve writing skills. This is a concept to improve the usability of LMS in English Learning teaching. In addition to the convenience of controlling student performance, this LMS is a form of advanced teaching application prototype. This concept also offers stakeholders to improve LMS features. Moodle, as an LMS that is commonly used almost all over the world, seems to also offer flexibility in modifying the application.